Revision of the genus Bradyporus Charpentier, 1825 (Orthoptera: Tettigoniidae: Bradyporinae) - Ünal, Mustafa (Zootaxa, 2017)
The genus Bradyporus Charpentier is taxonomically revised using information obtained from numerous recently collected specimens. Bradyporus is divided into two subgenera Bradyporus Charpentier s.str. and Callimenus Fischer von Waldheim. Five species groups are distinguished in the latter subgenus. Sixteen species and subspecies are listed. Bradyporus (Callimenus) multituberculatus multituberculatus (Fischer von Waldheim, 1833) and Bradyporus (Callimenus) multituberculatus montandoni (Burr, 1898) are designated subspecies for the first time. Previously synonymized Bradyporus (Callimenus) macrogaster skopjensis Karaman, 1961 is reinstated as a valid species. A new species, Bradyporus (Callimenus) gocmeni Ünal, sp. nov. from Eastern Turkey and the previously unknown female of Bradyporus (Callimenus) skopjensis Karaman, 1961 are described. A Neotype for Bradyporus (Callimenus) macrogaster longicollis (Fieber, 1853) is designated. Nomenclatural and taxonomical problems are discussed under the relevant taxa. Phylogenetic relationships based on morphology of the subgenera, species groups, and the species and subspecies of each species group are proposed. Morphological derived and ancestral characters are discussed. A key to the lower taxa of the genus is provided with 207 original figures including 3 distributional maps. A check-list of the lower taxa of the genus is given. Additionally the IUCN Red List statuses of the species and subspecies are included.